A cut-resistant composite yarn, a method of making the same, and a cut-resistant fabric

CN122879876APending Publication Date: 2026-10-09SHANTOU MINGDA TEXTILE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611292440.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]针对现有防切割复合纱线存在的金属-聚合物界面结合弱、结构稳定性差、功能单一、克重偏高、耐疲劳性不足的技术问题,本发明提供一种防切割复合纱线及其制备方法和防切割面料,通过引入经改性的海泡石纳米纤维,构建“刚性阻挡-能量吸收-应力分散”三级防切割体系,在提升防切割性能耐久性的同时,赋予纱线阻燃、耐磨、耐候等综合功能,降低金属丝用量与纱线克重,实现防护性能与穿戴舒适度的平衡

Benefits of technology

(1)本发明通过锌配位磷氮阻燃改性海泡石纳米纤维构建金属-聚合物界面过渡层,从本质上提升防切割复合纱线的结构稳定性与耐疲劳性能。一方面,改性海泡石表面的锌离子可与活化后的金属芯丝表面氧化层形成配位化学键,在无机相与有机相之间建立结合位点,大幅强化界面结合强度;另一方面,海泡石的一维纳米纤维结构可嵌入纤维表面微凹处与金属-纤维界面间隙中,通过物理嵌合增大纤维间及界面的摩擦力与咬合力,阻碍界面相对滑移,有效分散界面应力,显著延长防护制品的实际使用寿命;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of anti-cut composite yarn and its preparation method and anti-cut fabric, belong to textile material technical field.The composite yarn introduces zinc coordination phosphorus nitrogen flame-retardant sepiolite nanofiber obtained by three-step continuous chemical modification: first, natural sepiolite is acidified and activated, then grafted with silane coupling agent to introduce double bond, and finally, phosphorus-nitrogen flame-retardant monomer is grafted by in-situ radical polymerization and coordinated with zinc ions.Modified nanosepiolite can strengthen the metal-polymer interface bonding through coordination, improve the inter-fiber bonding force, and construct a three-level anti-cut synergistic system with metal core yarn and high-performance fibers.The obtained composite yarn has comprehensive properties such as anti-cut, flame-retardant, wear-resistant, bend-resistant, and seawater corrosion-resistant, and the yarn weight is lower than existing products of the same grade.The application also discloses the corresponding preparation method and knitted / woven anti-cut fabric, which can be widely used in protective gloves, work protective gear, and marine operation protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of textile materials technology, specifically to a cut-resistant composite yarn, its preparation method, and a cut-resistant fabric. Background Technology

[0002] With the development of fields such as industrial safety, outdoor operations, and emergency rescue, the performance requirements of protective textiles for workers are continuously increasing. Cut-resistant yarn, as a core raw material for products such as protective gloves, cut-resistant sleeves, and explosion-proof clothing, directly determines the protection level and wearing comfort of the products. Currently, cut-resistant yarns are mainly divided into two categories: one type is made of pure or blended high-performance fibers such as ultra-high molecular weight polyethylene and para-aramid, relying on the high modulus and high strength of the fibers to achieve cut resistance, but the upper limit of the protection level is relatively low. High-level products require a significant increase in weight, which can easily lead to stiffness and poor flexibility when worn; the other type is metal wire composite yarn, with stainless steel wire, alloy wire, etc. as the core layer, wrapped with high-performance fibers or chemical fibers, relying on the rigid barrier of metal to improve the protection level, which is the mainstream technical route for high-level products.

[0003] Patent application CN117418340A discloses a cut-resistant composite yarn, which uses double-twisted ultra-high molecular weight polyethylene fiber as the outer yarn, and alloy wire and tungsten wire wrapped with polyester to form the core yarn. After heating and softening the fiber, it is coated and molded. The resulting gloves can reach the US standard A8 cut-resistant level, but there are still several technical defects: First, the interfacial bonding force is weak and the structural stability is poor. The surface of ultra-high molecular weight polyethylene is highly inert, and heating and softening alone cannot fundamentally improve its bonding effect with the coating layer and the metal core yarn. Moreover, the difference in modulus between the metal and the polymer is huge, and the interfacial stress concentration is obvious. Repeated bending First, the metal wires are prone to slippage, breakage, or even exposure after folding, posing safety hazards and causing rapid degradation of protective performance. Second, the function is limited, only designed for cut protection, lacking properties such as flame retardancy and seawater corrosion resistance, making it unsuitable for complex working conditions such as metallurgy and marine operations. Adding additional functional layers would increase thickness and weight, reducing comfort. Third, the high metal content results in rigid yarn with high weight, leading to insufficient flexibility and fatigue when made into gloves, limiting the level of lightweighting. Fourth, the wear and fatigue resistance is insufficient, with fiber cohesion maintained solely by twist, making it prone to fuzzing and breakage due to long-term friction, and the metal core wires are easily degraded in corrosive environments.

[0004] Currently, improving the interfacial properties of metal composite yarns often involves simple treatment with silane coupling agents or the addition of ordinary toughening fillers, which have limited effectiveness and cannot simultaneously impart additional functionality. Therefore, developing novel composite yarns with excellent interfacial properties, high protection, and lightweight design is a pressing technical problem that needs to be solved in this field. Summary of the Invention

[0005] To address the technical problems of existing cut-resistant composite yarns, such as weak metal-polymer interface bonding, poor structural stability, limited functionality, high basis weight, and insufficient fatigue resistance, this invention provides a cut-resistant composite yarn, its preparation method, and a cut-resistant fabric. By introducing modified sepiolite nanofibers, a three-level cut-resistant system of "rigid blocking - energy absorption - stress dispersion" is constructed. This improves the durability of cut-resistant performance while endowing the yarn with comprehensive functions such as flame retardancy, abrasion resistance, and weather resistance, reducing the amount of metal wire and yarn basis weight, and achieving a balance between protective performance and wearing comfort. Specifically, the technical solution of this invention includes the following: a cut-resistant composite yarn comprising, from the inside out, a three-layer coaxial structure consisting of a metal core layer, a fiber-reinforced intermediate layer, and an outer covering layer; the fiber surface of the fiber-reinforced intermediate layer is loaded with zinc-coordinated phosphorus-nitrogen flame-retardant modified sepiolite nanofibers, and the zinc-coordinated phosphorus-nitrogen flame-retardant modified sepiolite nanofibers are dispersed in the matrix fibers of the outer covering layer.

[0006] The zinc-coordinated phosphorus-nitrogen flame-retardant modified sepiolite nanofibers were prepared through a three-step continuous chemical modification process, the specific steps of which are as follows: Acidification activation: Natural sepiolite was crushed and sieved, then placed in a 1-2 mol / L hydrochloric acid solution and refluxed at 80-100℃ for 2-4 hours to remove impurities such as carbonates, while simultaneously etching the fiber surface and increasing the number of surface hydroxyl groups; the product was filtered, washed with deionized water until the filtrate was neutral, vacuum dried at 80℃ for 12 hours, and then ground to obtain hydroxyl-activated sepiolite nanofibers (a-SNF).

[0007] Double bond grafting: Hydroxyl-activated sepiolite nanofibers were dispersed in an ethanol-water mixture (volume ratio 7:3) to prepare a suspension with a mass fraction of 5-8%, and ultrasonically dispersed for 30 min. The pH of the system was adjusted to 4-5 with glacial acetic acid, and the temperature was raised to 50-60℃. γ-methacryloyloxypropyltrimethoxysilane (KH570) was slowly added dropwise, and the reaction was maintained at this temperature for 3-5 h after the addition was complete. After the reaction, the nanofibers were centrifuged, washed three times with ethanol to remove unreacted coupling agent, and vacuum dried to obtain double bond modified sepiolite nanofibers (v-SNF). The amount of KH570 used was 15-25% of the mass of hydroxyl-activated sepiolite.

[0008] Functional polymerization and metal coordination: Double-bond modified sepiolite nanofibers were dispersed in deionized water to prepare a suspension with a mass fraction of 6-10%. After ultrasonic dispersion for 20 min, the suspension was transferred to a reactor. Diethylenetriaminepentamethylenephosphonic acid (DTPMPA) and acrylamide (AM) were added at a mass ratio of 2-3:1. The total mass of the monomers was 30-50% of the mass of the double-bond modified sepiolite, and the total mass of the monomers was the sum of the masses of acrylamide and DTPMPA. After stirring evenly, nitrogen gas was purged for 30 min to remove oxygen. Ammonium persulfate initiator was added (1-2% of the total monomer mass), and the temperature was raised to 70°C. At -80℃, the reaction was carried out at a constant temperature for 4-6 hours, during which acrylamide and double-bond modified sepiolite nanofibers underwent in-situ free radical polymerization. After polymerization, the temperature was lowered to room temperature, and zinc chloride solution was added with a zinc ion to phosphonic acid group molar ratio of 1:2-3. The mixture was stirred for coordination for 1-2 hours. The product was then placed in a dialysis bag and dialyzed for 72 hours to remove unreacted small molecules. Dialysis purification can remove ungrafted free copolymers, residual monomers, and excess inorganic salts from the system, ensuring the purity and surface activity of the modified sepiolite and avoiding impurities from degrading the subsequent interfacial bonding effect. After freeze-drying, zinc-coordinated phosphorus-nitrogen flame-retardant modified sepiolite nanofibers (Zn-P@SNF) were obtained.

[0009] Furthermore, the bimetallic core wire layer is formed by twisting one stainless steel microwire and one nickel-titanium alloy wire together. The diameter of the stainless steel microwire is 0.02-0.04 mm, and the diameter of the nickel-titanium alloy wire is 0.02-0.04 mm. The twist is 200-300 twists / 10 cm, and the twist direction is S-twist. The bimetallic core wire combines the high hardness of stainless steel with the high toughness of nickel-titanium alloy, and compared with a single tungsten / alloy wire, the bending fatigue resistance is improved by more than 40% at the same diameter.

[0010] Furthermore, the fiber-reinforced interlayer is composed of a blend of 200-600D high-modulus ultra-high molecular weight polyethylene (UHMWPE) fibers and 100-300D para-aramid fibers, twisted multiple times. The mass ratio of UHMWPE to para-aramid fibers is 3-5:1; the twist is 60-130 twists / 10cm, and the twist direction is Z-twist. UHMWPE provides the main cutting resistance and energy absorption, while para-aramid supplements heat resistance and creep resistance. The blending of the two can balance cut resistance and high-temperature resistance.

[0011] Furthermore, the outer coating layer is a flame-retardant polyester filament with a linear density of 25-100D, and the amount of zinc-coordinated phosphorus-nitrogen flame-retardant modified sepiolite nanofiber added to the flame-retardant polyester filament is 1.5-3.5wt%. The outer coating layer protects the internal fibers and metal wires on the one hand, and improves the abrasion resistance and flame retardancy of the yarn surface through dispersed nanofillers on the other hand.

[0012] Furthermore, by weight, the components in the composite yarn are as follows: 15-25 parts metal core filament layer, 50-60 parts fiber-reinforced intermediate layer, 15-25 parts outer coating layer, and 1-5 parts zinc-coated phosphorus-nitrogen flame-retardant modified sepiolite nanofibers. Compared with existing technologies of the same grade, the proportion of metal filament is reduced by approximately 30%, achieving lightweighting.

[0013] Furthermore, the outer coating layer adopts a bidirectional coating structure with an upper S-twist and a lower Z-twist, with a coating twist of 600-800 twists / 10cm. The bidirectional coating can offset the torsional stress of the single twist direction, improve the stability of the yarn structure, and reduce kinking during the weaving process.

[0014] Furthermore, the zinc-coordinated phosphorus-nitrogen flame-retardant modified sepiolite nanofibers on the fiber surface of the fiber-reinforced interlayer are loaded through an impregnation-drying process, with a loading amount of 2-4% of the fiber mass. Some nanofibers are embedded in micro-recesses on the fiber surface, while others protrude outwards, forming a mechanical interlock with the polymer of the outer coating layer during the coating process. Simultaneously, the side closer to the metal core filament forms coordination bonds with the oxide layer on the metal surface through zinc ions, achieving continuous reinforcement of the "metal-interlayer-outer coating" interface.

[0015] A cut-resistant composite yarn and its preparation method, comprising the following steps: S1. Preparation of modified sepiolite: Zinc-coordinated phosphorus and nitrogen flame-retardant modified sepiolite nanofibers were prepared according to the above three-step method. A dispersant was added to prepare a stable aqueous dispersion with a mass fraction of 3-5%. The dispersant was sodium dodecylbenzenesulfonate, and the amount used was 0.05%-0.2% of the total mass of the aqueous dispersion. S2. Fiber Pretreatment: Ultra-high molecular weight polyethylene fiber and para-aramid fiber are filamentally twisted in a certain proportion and continuously passed through the above-mentioned aqueous dispersion. The fibers are then impregnated with ultrasonic assistance at 20-30kHz for 2-5 seconds to promote uniform adsorption of nanofillers on the fiber surface. Subsequently, the fibers are extruded through rollers to control the liquid extraction rate to 70-90%. Then, the fibers are dried in a three-stage gradient (60℃→70℃→80℃) to remove moisture, so that the modified sepiolite is firmly loaded on the fiber surface, resulting in pretreated mixed fibers. S3. Core wire preparation: Stainless steel microwires and nickel-titanium alloy wires are twisted together on a double twister, and the twist and twist direction are controlled to obtain a metal core wire layer. Before coating, the metal core wire layer is subjected to atmospheric pressure air plasma surface treatment with a treatment power of 100-200W and a treatment time of 10-20s to etch the surface and introduce hydroxyl groups to enhance coordination binding sites. S4, Double-twisted intermediate layer: The pretreated mixed fibers are double-twisted on a winding double-twisting machine, and the twist and twist direction are controlled to obtain a fiber-reinforced intermediate layer; S5. Composite Coating: The fiber-reinforced intermediate layer and the plasma-treated metal core wire layer are fed together into a hollow spindle coating machine; at the same time, flame-retardant polyester filament mixed with modified sepiolite is used as the outer wrapping yarn, and bidirectional coating is carried out using upper and lower double spindle positions to control the coating twist and obtain a composite yarn semi-finished product. S6. Heat setting: The composite yarn semi-finished product is heat set in a continuous heat setting box at 50-70℃, with the traction speed controlled at 15-25m / min. This eliminates the internal stress of the yarn, stabilizes the structural dimensions, and finally yields the finished cut-resistant composite yarn.

[0016] A cut-resistant fabric is made by blending the above-mentioned cut-resistant composite yarn with auxiliary yarn; the auxiliary yarn is made by twisting 20-80D spandex yarn as core yarn and 75-150D polyester yarn or 70-140D nylon yarn as outer yarn, the twisting method is Z twist, the twist degree is 250-450 twists / 10cm, and the spandex elongation is set to 1.5-2.5 times.

[0017] Furthermore, the fabric can be prepared as a knitted fabric, woven using the 13GU2 weave method, with a weight of 180-250 g / m². 2 It is suitable for flexible products such as protective gloves and sleeves; it can also be made into woven fabrics, using plain or twill weave structures, with a weight of 200-280 g / m². 2 It is suitable for cut-resistant workwear, explosion-proof blankets, anti-theft bags, etc.

[0018] Furthermore, the fabric surface may be coated with nitrile, PU or latex impregnation coating. After the coating is applied, the fabric's cut resistance rating remains above EN3884, while also improving its anti-slip, waterproof and chemical resistance properties.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention constructs a metal-polymer interface transition layer using zinc-coordinated phosphorus-nitrogen flame-retardant modified sepiolite nanofibers, which fundamentally improves the structural stability and fatigue resistance of the cut-resistant composite yarn. On the one hand, zinc ions on the surface of modified sepiolite can form coordination chemical bonds with the oxide layer on the surface of the activated metal core wire, establishing binding sites between the inorganic and organic phases and significantly strengthening the interfacial bonding strength; on the other hand, the one-dimensional nanofiber structure of sepiolite can be embedded in the micro-concave areas on the fiber surface and the gaps between the metal-fiber interface, increasing the friction and interlocking forces between fibers and the interface through physical interlocking, hindering relative slippage of the interface, effectively dispersing interfacial stress, and significantly extending the actual service life of the protective product; (2) A three-level synergistic anti-cutting system is formed by rigid blocking of metal core wire, energy absorption of high-performance fiber, and crack pinning of nanofiller, which greatly improves the protection efficiency per unit weight. First, the metal core wire directly blocks the blade from cutting in and consumes the main cutting energy by relying on its high hardness. Second, the ultra-high molecular weight polyethylene and para-aramid blended fiber in the middle layer absorbs the remaining energy and disperses the stress to the surrounding area through fiber stretching, deformation and fracture. Finally, the modified sepiolite loaded on the fiber surface and in the coating layer enhances the cohesion between fibers, deflects and pins the crack propagation path, and prevents local rapid failure caused by stress concentration. Under the synergistic effect of the three, a high level of anti-cutting performance can be stably achieved under the premise of reducing the amount of metal wire and reducing the yarn linear density, realizing the unity of high protection, lightweight and softness, and improving the wearing comfort and operation flexibility of protective gloves and other products. (3) The present invention achieves synergistic gains through multi-step functionalization design of nanofillers, which can adapt to the protection requirements of multiple working conditions without the need to add a large number of functional additives. In terms of flame retardant performance, the phosphorus-based components grafted onto modified sepiolite catalyze the condensation phase to form char, creating a more stable and denser graphitized char layer, which further enhances the heat insulation and oxygen barrier effects. When phosphorus-nitrogen flame retardants decompose under heat, they release non-combustible gases such as ammonia (NH3) and nitrogen (N2). These gases can dilute the concentration of combustible gases in the flame zone. At the same time, the phosphorus-containing free radicals generated by their decomposition can capture highly active free radicals in the combustion chain reaction, thereby interrupting the combustion reaction. Coordinated zinc ions catalyze the densification of the char layer structure, and the silica-oxygen skeleton of sepiolite itself serves as a rigid support for the char layer, synergistically constructing a gas-phase-condensed-phase dual-layer flame retardant system, giving the yarn excellent flame retardant and heat resistance properties. In terms of abrasion resistance and weather resistance, the high hardness of sepiolite improves the abrasion resistance of the yarn surface, and the layered silicate structure can shield ultraviolet rays and prevent the penetration of seawater and acid and alkali media. Combined with the dense interface structure to protect the internal metal core filaments, it significantly improves the performance stability of the yarn in complex environments, while avoiding the problems of poor compatibility and mechanical property degradation caused by the compounding of multiple additives. (4) This invention uses natural sepiolite as the core modified filler, combined with a mild and controllable three-step modification route and a preparation process compatible with existing production lines, which has excellent industrial applicability. Sepiolite is a natural silicate mineral with abundant reserves and controllable costs, resulting in low overall costs; the three-step chemical modification reaction conditions are mild, the reaction sites are clear and controllable, and there are no high-risk reaction steps, so it can be prepared in batches in general chemical equipment; the yarn preparation process is compatible with traditional twisting, covering, heat setting and other textile equipment, and can be put into production without large-scale modification of production lines. Moreover, the modified sepiolite has high efficiency, and significant performance gains can be achieved with a low addition amount, with controllable increase in overall production costs, giving it good market competitiveness. Detailed Implementation

[0020] The technical solution of the present invention will be clearly and completely described below through embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] Unless otherwise stated, all raw materials and reagents used in this invention are commercially available or can be prepared by known methods.

[0022] Main raw materials: natural sepiolite (industrial grade, aspect ratio 50-80); γ-methacryloyloxypropyltrimethoxysilane (KH570, industrial grade); diethylenetriaminepentamethylenephosphonic acid (DTPMPA, 50% aqueous solution, industrial grade); acrylamide (AM, analytical grade); ammonium persulfate (APS, analytical grade); zinc chloride (analytical grade); 400D high-cut-resistant UHMWPE fiber (ZT50 series); 150D para-aramid fiber (aramid 1414); 304 stainless steel microfilaments, nickel-titanium alloy wires, nickel-tungsten alloy wires (diameter 0.02-0.04mm, industrial grade); 50D flame-retardant polyester filaments (industrial grade); 40D spandex filaments, 100D polyester filaments (industrial grade); fumed nano silica (hydrophilic, particle size 15nm); ammonium polyphosphate (APP, degree of polymerization n>1000, industrial grade).

[0023] Example 1 Preparation of Zinc-Coordinated Phosphorus-Nitrogen Flame-Retardant Modified Sepiolite Nanofibers (1) Acidification activation: Natural sepiolite was crushed and passed through a 200-mesh sieve. 100g was weighed and added to 800mL of 1.5mol / L hydrochloric acid solution. The mixture was refluxed at 90℃ and stirred for 3h. After filtration, it was washed with deionized water until the filtrate was neutral. It was then vacuum dried at 80℃ for 12h and ground to obtain hydroxyl-activated sepiolite nanofibers. (2) Double bond grafting: Weigh 50g of hydroxyl-activated sepiolite and disperse it in an ethanol-water mixture (volume ratio 7:3) to prepare a 6% mass fraction suspension. Sonicate the suspension for 30min. Adjust the pH to 4.5 with glacial acetic acid, raise the temperature to 55℃, and slowly add 10g of KH570. After the addition is complete, keep the temperature constant for 4h. After the reaction is complete, centrifuge at 8000rpm for 10min, wash three times with anhydrous ethanol, and vacuum dry to obtain double bond modified sepiolite nanofibers. (3) Functional polymerization and metal coordination: Weigh 50g of double bond modified sepiolite, disperse it in 700mL of deionized water, sonicate for 20min and then transfer it to a reaction vessel; add 14g of DTPMPA and 6g of AM, stir to dissolve; purge with nitrogen for 30min to remove oxygen, add 0.3g of APS initiator, heat to 75℃ and react at a constant temperature for 5h; after the reaction is completed, cool down to 25℃, add about 98mL of 0.5mol / L anhydrous zinc chloride aqueous solution (containing about 0.049mol of zinc ions, the molar ratio of zinc ions to phosphonic acid groups in the system is 1:2.5), stir for coordination for 1.5h; put the product into a dialysis bag with a molecular weight cutoff of 8000-14000 and dialyze for 72h, freeze dry to obtain zinc coordinated phosphorus nitrogen flame retardant modified sepiolite nanofibers.

[0024] Preparation of cut-resistant composite yarn S1. Prepare a modified sepiolite aqueous dispersion with a mass fraction of 4% and add 0.1% sodium dodecylbenzenesulfonate as a dispersant; S2. Fiber Pretreatment: 400D DUHMWPE fiber and 150D para-aramid fiber are filament-by-filament at a mass ratio of 4:1 and continuously passed through the above dispersion solution. The fibers are then ultrasonically impregnated for 3 seconds with 25kHz assistance, and the liquid extraction rate is controlled at 80% using rollers. After drying in three gradient stages at 60℃, 70℃, and 80℃, pretreated mixed fibers with surface-loaded modified sepiolite are obtained, with a loading amount of 3% of the fiber mass. S3. Core wire preparation: Take one 0.03mm diameter 304 stainless steel microwire and one 0.03mm diameter nickel-titanium alloy wire, and twist them together on a doubling twister with an S-twist of 250 twists / 10cm to obtain a metal core wire layer; before coating, perform atmospheric pressure air plasma treatment with a power of 150W and a treatment time of 15s. S4, Double Twist Intermediate Layer: The pretreated mixed fibers are double twisted in Z-twist, with a twist of 90 twists / 10cm, to obtain a fiber-reinforced intermediate layer; S5. Composite Coating: The fiber-reinforced intermediate layer and the metal core filament layer are fed into a hollow spindle coating machine in parallel. 50D flame-retardant polyester filament mixed with 2.5wt% modified sepiolite is used as the outer yarn. The yarn is coated in both directions with upper S twist and lower Z twist. The coating twist is 700 twists / 10cm to obtain a composite yarn semi-finished product. S6. Heat setting: The semi-finished product is continuously heat-set at 60℃ with a traction speed of 20m / min to obtain the finished cut-resistant composite yarn.

[0025] The mass percentage of the finished yarn components is as follows: 20 parts metal core layer, 55 parts fiber-reinforced intermediate layer, 21 parts outer covering layer, and 4 parts modified sepiolite.

[0026] Preparation of cut-resistant knitted fabrics Auxiliary yarn preparation: 40D spandex yarn as core, 100D polyester yarn as outer sheath, Z twist plus 350 twists / 10cm, spandex elongation 2.0 times.

[0027] Using a 13G U2 knitting machine, the composite yarn and auxiliary yarn are blended in a 1:1 ratio to obtain a knitted cut-resistant fabric with a weight of approximately 220 g / m². 2 .

[0028] Example 2 The embodiments are basically the same as Embodiment 1, except that: the metal core filament layer uses stainless steel microwires with a diameter of 0.025mm and nickel-titanium alloy wires with a twist of 260 twists / 10cm; the mass ratio of the finished yarn components is: 18 parts of metal core filament layer, 58 parts of fiber-reinforced intermediate layer, 20 parts of outer covering layer, and 4 parts of modified sepiolite.

[0029] The remaining raw materials and processes are the same as in Example 1.

[0030] Example 3 This embodiment is basically the same as embodiment 1, except that: in the fiber-reinforced intermediate layer, the mass ratio of UHMWPE fiber to para-aramid fiber is 3:1, and the twist is 95 twists / 10cm, which increases the proportion of aramid to enhance the heat resistance and flame retardant properties.

[0031] The remaining raw materials and processes are the same as in Example 1.

[0032] Example 4 This embodiment is basically the same as Embodiment 1, except that: the modified sepiolite loading on the fiber surface is 4%, and the amount added to the outer coating layer is 3.5wt%; the total proportion of modified sepiolite in the finished yarn is 5 parts, corresponding to 19 parts of the metal core layer, 54 parts of the fiber reinforcement intermediate layer, and 22 parts of the outer coating layer.

[0033] The remaining raw materials and processes are the same as in Example 1.

[0034] Example 5 This embodiment is basically the same as that of embodiment 1, except that in step 1 (3), the coordination molar ratio of zinc ions to phosphonic acid groups is adjusted to 1:2.

[0035] The remaining raw materials and processes are the same as in Example 1.

[0036] Example 6 This embodiment is basically the same as embodiment 1, except that in step S3, the plasma surface treatment process of the metal core wire is omitted, and the wire is directly wrapped.

[0037] The remaining raw materials and processes are the same as in Example 1.

[0038] Example 7 This embodiment is basically the same as embodiment 1, except that: in the fiber-reinforced intermediate layer, the mass ratio of UHMWPE fiber to para-aramid fiber is 5:1, and the twist is 85 twists / 10cm.

[0039] The remaining raw materials and processes are the same as in Example 1.

[0040] Example 8 This embodiment is basically the same as that of embodiment 1, except that the amount of zinc-coordinated phosphorus-nitrogen flame-retardant modified sepiolite nanofiber added in the flame-retardant polyester filament of the outer coating layer is 1.5 wt%.

[0041] The remaining raw materials and processes are the same as in Example 1.

[0042] Example 9 This embodiment is basically the same as Embodiment 1, except that the mass ratio of the finished yarn components is as follows: 15 parts of metal core filament layer, 60 parts of fiber-reinforced intermediate layer, 25 parts of outer coating layer, and 1 part of zinc-coordinated phosphorus-nitrogen flame-retardant modified sepiolite nanofiber.

[0043] The remaining raw materials and processes are the same as in Example 1.

[0044] Example 10 This embodiment is basically the same as Embodiment 1, except that the mass ratio of the finished yarn components is as follows: 25 parts of metal core filament layer, 50 parts of fiber-reinforced intermediate layer, 15 parts of outer coating layer, and 5 parts of zinc-coordinated phosphorus-nitrogen flame-retardant modified sepiolite nanofiber.

[0045] The remaining raw materials and processes are the same as in Example 1.

[0046] Comparative Example 1 Composite yarns are prepared using existing technologies: (1) Take 480DZT50 series UHMWPE fiber, twist it twice with a twister, and the twist is 110 twists / 10cm; (2) Take a nickel-tungsten alloy wire with a diameter of 0.03mm and a tungsten wire with a diameter of 0.04mm, wrap it with 75D polyester filament to form a core wire, S twist, twist degree 280 twists / 10cm; (3) After the double-twisted UHMWPE fiber is heated by infrared at 65°C, it is fed together with the core yarn into the outer polyester, and the bidirectional wrapping twist is 750 twists / 10cm to obtain composite yarn.

[0047] The mass percentage of the finished product components is as follows: 52 parts UHMWPE, 7 parts alloy wire, 23 parts tungsten wire, and 18 parts polyester.

[0048] Knitted fabrics were prepared using the same process as in Example 1.

[0049] Comparative Example 2 The method is basically the same as in Example 1, except that: natural sepiolite powder without any chemical modification is used directly to replace zinc-coordinated phosphorus and nitrogen flame-retardant modified sepiolite in equal amounts, and is added to the fiber surface and the outer coating layer respectively. The amount added and the loading are the same as in Example 1.

[0050] The remaining processes are the same as in Example 1.

[0051] Comparative Example 3 The results are basically the same as in Example 1, except that no sepiolite or nanofillers are added, the fibers are not impregnated or pretreated, and the outer coating is made of pure flame-retardant polyester filament.

[0052] The remaining processes are the same as in Example 1.

[0053] Comparative Example 4 The process is basically the same as in Example 1, except that: only the first two steps of modification are performed on the sepiolite, and the third step of in-situ free radical polymerization and zinc coordination is not performed. Double bond modification of sepiolite is used directly, and the amount added and the loading are the same as in Example 1.

[0054] The remaining processes are the same as in Example 1.

[0055] Comparative Example 5 The process is basically the same as in Example 1, except that: fumed silica is used instead of sepiolite, and the modification is carried out in the same three-step process to obtain zinc-coordinated phosphorus-nitrogen modified silica, which replaces the modified sepiolite in equal amounts. The amount added and the loading are the same as in Example 1.

[0056] The remaining processes are the same as in Example 1.

[0057] Comparative Example 6 The results are basically the same as in Example 1, except that the modified sepiolite is only added to the polyester filament of the outer coating layer, the fiber-reinforced intermediate layer is not impregnated, and there is no modified sepiolite load on the fiber surface.

[0058] The remaining processes are the same as in Example 1.

[0059] Comparative Example 7 The process is basically the same as in Example 1, except that commercial ammonium polyphosphate (APP) flame retardant is used to replace the modified sepiolite in an equal amount and is only added to the outer coating layer, and the fibers are not impregnated.

[0060] The remaining processes are the same as in Example 1.

[0061] Performance testing: 1. Cut resistance performance: Referring to EN388:2016 standard, the cutting index of the specimen is tested using the coupled cutting test method, and the corresponding cut resistance performance level is determined. 2. Interface bonding performance: The maximum load of the metal core wire pulled out of the yarn was tested using a universal testing machine, and the metal wire pull-out force was used to characterize the metal-polymer interface bonding strength. 3. Bending fatigue resistance: The yarn sample was repeatedly bent 10,000 times under constant tension. The cutting index after bending was tested and the performance retention rate was calculated to evaluate the fatigue stability of the yarn. 4. Flame retardant performance: Referring to GB / T5454-1997 standard, the limiting oxygen index of the sample is tested using the oxygen index method to quantitatively evaluate the flame retardant performance level; 5. Abrasion resistance: Referring to EN388:2016 standard, the number of friction cycles before the sample is worn through is tested using an abrasion tester, and the abrasion resistance level is determined accordingly. 6. Seawater corrosion resistance: The sample was immersed in a 3.5% sodium chloride simulated seawater solution for 7 days. The cutting index after immersion was tested and the performance retention rate was calculated to evaluate the environmental weather resistance.

[0062] The test results are shown in Table 1.

[0063]

[0064] Data shows that Comparative Example 1 achieves its cut index by relying on a high proportion of metal wires, but its yarn linear density is significantly higher. In contrast, Example 1 of this invention, with a yarn linear density much lower than Comparative Example 1, still achieves a higher cut index, demonstrating improved protection efficiency per unit weight and achieving the beneficial effects of yarn lightweighting and improved wearability. Comparative Example 3, without nanofillers, shows a significant decrease in the cut index, indicating that nanofillers are a necessary component of Level 3 protection. Comparative Example 2, using unmodified sepiolite, shows only a limited increase in the cut index, stemming from the strong polarity and tendency to agglomerate of natural sepiolite, which introduces defects into the fiber matrix, failing to effectively enhance its reinforcing effect. Comparative Example 4, having only completed the first two modification steps, shows a slight increase in the cut index, but it remains lower than the complete solution, indicating that the third step of polymerization coordination not only imparts functionality but also improves the compatibility between nanofillers and fibers through grafting organic chains. Comparative Example 5… Using zero-dimensional nano-silica for the same modification resulted in performance weaker than one-dimensional sepiolite, confirming the irreplaceable role of sepiolite structure in crack deflection and stress transfer. Comparative Example 6 lacked the surface load of the intermediate fiber layer, and the cutting index dropped significantly, proving that sepiolite embedded in the micro-concavities on the fiber surface and in the gap between the metal-fiber interface increases the friction and interlocking force between fibers and the interface, which is the key structure for improving the friction between fibers and constructing multi-level protection. Comparative Example 7 used ordinary flame retardants and did not have any cut resistance gain at all, but instead degraded the mechanical properties of the matrix.

[0065] The wire pull-out force of Example 1 is significantly improved compared to Comparative Example 1, and the performance retention rate after 10,000 bends is also much higher than that of Comparative Example 1. This fundamentally improves the structural stability of the yarn, extends the service life of protective products, and reduces the safety risk of punctures from exposed wires. This is because zinc ions can simultaneously form coordination with oxygen atoms in the oxide layer of the metal surface and phosphonic acid groups on the surface of sepiolite, establishing a metal-polymer connection bridge at the molecular level; at the same time, one-dimensional sepiolite fibers interpenetrate in the interfacial gaps, forming microscopic mechanical interlocking, further dispersing interfacial stress. In the control experiments, the zero-dimensional nanofiller in Comparative Example 5 could not form an effective fibrous interlocking structure, so its pull-out force and bending resistance were weaker than those of the present invention. Comparative Example 6 lacked an intermediate layer interface load, so the nanofiller could not act on the metal-fiber interface, and the interface reinforcement effect was greatly reduced. In Example 6, after omitting the metal wire plasma activation step, both the pull-out force and bending resistance decreased because the number of hydroxyl sites on the metal surface was reduced, and the coordination binding effect was weakened. In Example 7, as the proportion of high-modulus UHMWPE increased, the yarn cutting index increased slightly, and the proportion of aramid decreased, which caused the limiting oxygen index to decrease slightly. The overall comprehensive performance remained excellent. In Example 8, reducing the amount of modified sepiolite added to the outer coating layer resulted in a mild decline in interface reinforcement, flame retardancy, and weather resistance compared to the optimal ratio. In Examples 9-10, the low-metal, high-fiber solution was lighter, and the cutting index decreased slightly but still reached the European standard level 4. The high-metal solution had stronger protective performance and a corresponding increase in linear density. All indicators were still significantly better than the existing comparative examples.

[0066] In terms of flame retardancy, the limiting oxygen index of the embodiments is much higher than that of the prior art Comparative Example 1, and it can pass the rigorous flame spread test, which is different from the single action mode of traditional additive flame retardants. In the control experiment, although the oxygen index of the commercial flame retardant used in Comparative Example 7 can be improved, it cannot reach the flame retardancy level of the present invention, and it does not have the functions of cutting resistance and interface reinforcement. Instead, it reduces the mechanical properties of the yarn, which confirms the multi-functional synergistic advantage of the modified filler of the present invention. In terms of abrasion resistance, the abrasion resistance level of the embodiments is generally better than that of the unfilled and unmodified filler solutions. This is because the high hardness of sepiolite itself can improve the abrasion resistance of the yarn surface. At the same time, the fiber is not easy to pull out and fuzz after the interface bonding is reinforced. The two work together to improve the abrasion life. In terms of seawater corrosion resistance, the performance retention rate of the embodiments after seawater immersion is much higher than that of the prior art. On the one hand, the layered silicate structure of sepiolite can physically block the penetration of corrosive media. On the other hand, the dense interface structure reduces the path of corrosive media to the metal core wire, which together protects the internal metal core wire from corrosion and improves the performance stability of the yarn under complex working conditions such as marine and humid conditions.

[0067] The embodiments described above provide a detailed explanation of the technical solutions and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Various changes and modifications can be made to the present invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed.

Claims

1. A cut-resistant composite yarn, characterized in that, The cut-resistant composite yarn comprises, from the inside out, a metal core layer, a fiber-reinforced intermediate layer, and an outer coating layer. The fiber surface of the fiber-reinforced intermediate layer is loaded with zinc-coordinated phosphorus-nitrogen flame-retardant modified sepiolite nanofibers, and the zinc-coordinated phosphorus-nitrogen flame-retardant modified sepiolite nanofibers are dispersed in the matrix fibers of the outer coating layer. The zinc-coordinated phosphorus-nitrogen flame-retardant modified sepiolite nanofibers are prepared through the following steps: (1) Natural sepiolite was refluxed in hydrochloric acid solution, filtered and washed until neutral, and dried to obtain hydroxyl-activated sepiolite nanofibers. (2) Hydroxyl activated sepiolite nanofibers were dispersed in an ethanol-water system, γ-methacryloxypropyltrimethoxysilane was added, the pH was adjusted to weak acidity, and the reaction was carried out at a constant temperature. After centrifugation and washing, double bond modified sepiolite nanofibers were obtained. (3) The double bond modified sepiolite nanofibers were dispersed in deionized water, and diethylenetriaminepentimethylenephosphonic acid, acrylamide and initiator were added. The in-situ free radical polymerization reaction was carried out under nitrogen protection. After the reaction was completed, zinc salt was added for coordination reaction. The product was dialyzed and freeze-dried to obtain zinc coordinated phosphorus nitrogen flame retardant modified sepiolite nanofibers.

2. The cut-resistant composite yarn according to claim 1, characterized in that, The metal core layer is formed by twisting one stainless steel microwire and one nickel-titanium alloy wire together. The diameter of the stainless steel microwire is 0.02-0.04 mm, and the diameter of the nickel-titanium alloy wire is 0.02-0.04 mm. The twist is 200-300 twists / 10 cm, and the twist direction is S-twist. The fiber-reinforced intermediate layer is formed by blending and twisting 200-600D high-modulus ultra-high molecular weight polyethylene fiber and 100-300D para-aramid fiber. The mass ratio of ultra-high molecular weight polyethylene fiber to para-aramid fiber is 3-5:

1. The twist of the fiber-reinforced intermediate layer is 60-130 twists / 10 cm, and the twist direction is Z-twist.

3. The cut-resistant composite yarn according to claim 1, characterized in that, The outer coating is a flame-retardant polyester filament with a linear density of 25-100D, and the amount of zinc-coordinated phosphorus-nitrogen flame-retardant modified sepiolite nanofiber added to the flame-retardant polyester filament is 1.5-3.5wt%.

4. The cut-resistant composite yarn according to claim 1, characterized in that, By mass fraction, the components in the composite yarn are as follows: 15-25 parts metal core filament layer, 50-60 parts fiber-reinforced intermediate layer, 15-25 parts outer coating layer, and 1-5 parts zinc-coordinated phosphorus-nitrogen flame-retardant modified sepiolite nanofibers.

5. The cut-resistant composite yarn according to claim 1, characterized in that, The outer coating layer adopts a bidirectional coating structure with upper S twist and lower Z twist, and the coating twist is 600-800 twists / 10cm.

6. The cut-resistant composite yarn according to claim 1, characterized in that, In step (1), the concentration of hydrochloric acid is 1-2 mol / L, the reflux temperature is 80-100℃, and the reflux time is 2-4 h; in step (2), the amount of γ-methacryloyloxypropyltrimethoxysilane is 15-25% of the mass of hydroxyl-activated sepiolite, the reaction temperature is 50-60℃, the reaction time is 3-5 h, and the pH is 4-5; in step (3), the mass ratio of diethylenetriaminepentamethylenephosphonic acid to acrylamide is 2-3:1, the total mass of monomers is 30-50% of the mass of double-bond modified sepiolite, the total mass of monomers is the total mass of acrylamide and diethylenetriaminepentamethylenephosphonic acid, the initiator is ammonium persulfate, the amount of initiator is 1-2% of the total mass of monomers, the polymerization temperature is 70-80℃, and the polymerization time is 4-6 h; the zinc salt is zinc chloride, the molar ratio of zinc ions to phosphonic acid groups is 1:2-3, the coordination temperature is room temperature, and the coordination time is 1-2 h.

7. The cut-resistant composite yarn according to claim 1, characterized in that, The zinc-coordinated phosphorus-nitrogen flame-retardant modified sepiolite nanofibers on the fiber surface of the fiber-reinforced intermediate layer are loaded through an impregnation-drying process, with a loading amount of 2-4% of the fiber mass.

8. A method for preparing the cut-resistant composite yarn as described in any one of claims 1-7, characterized in that, Includes the following steps: S1. Prepare zinc-coordinated phosphorus and nitrogen flame-retardant modified sepiolite nanofibers according to the steps described above, add a dispersant to them, and prepare an aqueous dispersion with a mass fraction of 3-5%, wherein the dispersant is sodium dodecylbenzenesulfonate, and the amount used is 0.05%-0.2% of the total mass of the aqueous dispersion; S2. After the ultra-high molecular weight polyethylene fiber and para-aramid fiber are filamentally combined, they are continuously passed through the aqueous dispersion, ultrasonically impregnated and squeezed, and then dried in stages at low temperature at 60-80℃ to load modified sepiolite onto the fiber surface, thus obtaining pretreated mixed fiber. S3. Twist stainless steel microwires and nickel-titanium alloy wires together to obtain a metal core wire layer; S4. Twist the pretreated mixed fibers twice to obtain a fiber-reinforced intermediate layer; S5. After the fiber-reinforced intermediate layer and the metal core filament layer are fused together, they are fed into the coating machine. At the same time, flame-retardant polyester filament mixed with modified sepiolite is added as the outer coating layer. The two-way coating process is carried out to obtain a composite yarn semi-finished product. S6. The composite yarn semi-finished product is subjected to continuous heat setting at 50-70℃, with a traction speed of 15-25m / min, to obtain the finished cut-resistant composite yarn.

9. The method for preparing the cut-resistant composite yarn according to claim 8, characterized in that, In step S2, the ultrasonic impregnation frequency is 20-30kHz, and the single-pass impregnation time is 2-5s; the liquid rolling rate is controlled at 70-90%; the drying adopts a three-stage gradient heating, with temperatures of 60℃, 70℃, and 80℃ respectively; before the coating in step S5, the metal core wire layer is subjected to atmospheric pressure air plasma surface treatment with a treatment power of 100-200W and a treatment time of 10-20s.

10. A cut-resistant fabric, characterized in that, The fabric is made of a blend of the anti-cut composite yarn as described in any one of claims 1-7 and the auxiliary yarn; the auxiliary yarn is made by twisting 20-80D spandex yarn as the core yarn and 75-150D polyester yarn or 70-140D nylon yarn as the outer yarn, with the twisting method being Z-twist and the twist degree being 250-450 twists / 10cm; the anti-cut fabric is a knitted fabric, woven using the 13GU2 weave method, with a weight of 180-250g / m². 2 Alternatively, it may be a woven fabric, using a plain or twill weave, with a weight of 200-280 g / m². 2 .

Citation Information

Patent Citations

  • Anti-cutting composite yarn and product prepared from same

    CN117418340A